Analisis Meteorologi Awan Penyebab Angin Kencang: Studi Kasus Klaten, 18 November 2024 - Febby Debora Abigael; Ahmad Hanif Al'aziz; Arya Zaki Ramadhan; Achmad Zakir; Aditya Mulya (Journal of Computation Physics and Earth Science (JoCPES), 2025)
Klaten Regency, Central Java, has frequently experienced extreme convective weather in the form of strong surface winds that have caused damage to residential areas and public facilities. This study analyzed a strong wind event that occurred on 18 November 2024 between 15:30 and 16:30 Local Time, which had significant impacts across several sub-districts in Klaten. The objective of this research was to evaluate the atmospheric dynamics and cloud characteristics responsible for the event. A descriptive–analytical approach was applied using secondary data, including the Dipole Mode Index, the Madden–Julian Oscillation Diagram, streamline map, and atmospheric stability indices to assess atmospheric dynamics. In addition, dual-polarization weather radar products were used to examine convective cloud structure, vertical development, wind convergence and divergence patterns, and indications of vortex formation. The results showed that the event was dominated by a rapidly developing Cumulonimbus cloud system, with maximum reflectivity values reaching approximately 69 dBZ and cloud-top heights of about 10 km. Low-level wind convergence and horizontal wind shear played a critical role in triggering deep convection. Atmospheric stability indices indicated sufficiently unstable conditions, although instability was not extreme. Doppler radar analysis revealed strong updraft–downdraft interactions, intense convergence–divergence patterns, and vortex formation during the mature stage of the storm.